Role of Siglecs in viral infections: A double-edged sword interaction. (April 2023) - Raïch-Regué, Dàlia; Resa-Infante, Patricia; Gallemí, Marçal; Laguia, Fernando; Muñiz-Trabudua, Xabier; Muñoz-Basagoiti, Jordana; Perez-Zsolt, Daniel; Chojnacki, Jakub; Benet, Susana; Clotet, Bonaventura; Martinez-Picado, Javier; Izquierdo-Useros, Nuria
Abstract: Sialic-acid-binding immunoglobulin-like lectins are cell surface immune receptors known as Siglecs that play a paramount role as modulators of immunity. In recent years, research has underscored how the underlaying biology of this family of receptors influences the outcome of viral infections. While Siglecs are needed to promote effective antiviral immune responses, they can also pave the way to viral dissemination within tissues. Here, we review how recent preclinical findings focusing on the interplay between Siglecs and viruses may translate into promising broad-spectrum therapeutic interventions or key biomarkers to monitor the course of viral infections.